Perubahan Komunikasi Orang Tua Terhadap Anak Di Era Digital - Perdian Muhamad Thoha; Rizki Puja Kurniawan; Andhita Risko Faristiana (Student Scientific Creativity Journal, 2023)
Communication between parents and children is an important aspect in the formation of healthy family relationships. However, with the advent of digital technology, communication patterns between parents and children have changed significantly. This article discusses changes in parent-child communication in the digital era and the impact it has on parent-child relationships. This article also discusses the positive and negative impacts of changes in parent-child communication as well as strategies that can be taken by parents to optimize communication with children in the digital era. The purpose of writing this article is to provide information and advice for parents who want to maintain good communication relations with their children in the digital age and emphasize the importance of effective communication in family relationships. In this article, we use sources from scientific and research journals related to changes in parent-child communication in the digital era and their impact on family relationships.